Analisis Penggunaan Media Sosial pada Pemberian Layanan Informasi - Ahmad Alpin Sahri; Elismayanti Rambe (PT. Willy Print Art, 2024)
The use of social media by the government for various purposes to increase public interaction with the government, especially students studying science, is increasing rapidly at this time. Social media is used as an information and communication service. This aims to help the community, especially female students who study science. This research uses the critical review method. The results of the research examined show that social media is very helpful in providing information services by teachers in schools. Information services with the help of media, both online and offline, help students more easily understand the information provided and are able to inspire guidance teachers to be creative in making interesting media.